Pendekatan Integratif Untuk Peningkatan Efektivitas Layanan dan Operasional Bengkel Otomotif: Systematic Literature Review - Siti Ruqaiyah Baharuddin; Syakia Muflihat (Universitas Muhammadiyah Metro, 2026)
The increasing number of motor vehicles has led to higher demand for automotive workshop services, requiring workshops to improve both service quality and operational efficiency. However, many automotive workshops still face operational problems such as long service waiting times, inefficient workflows, inconsistent service quality, and non-value-added activities. This study aims to identify and analyze various approaches used to improve service quality and operational efficiency in automotive workshops through a Systematic Literature Review (SLR). The study reviewed 15 scientific articles published between 2020 and 2025 related to automotive workshop services, operational improvement, and quality management methods. The analysis focused on approaches such as Service Quality (SERVQUAL), Importance Performance Analysis (IPA), Lean Service, Quality Function Deployment (QFD), Value Stream Mapping (VSM), Six Sigma, Service Blueprint, TRIZ, and Design Thinking. The results show that SERVQUAL is the most widely used method for identifying service quality gaps, especially in responsiveness and reliability dimensions. However, integrated approaches combining service quality methods with operational improvement methods such as Lean Service, VSM, and Six Sigma provide more comprehensive solutions for improving workshop performance. These approaches are effective in reducing operational waste, improving workflow efficiency, minimizing service variability, and enhancing service innovation. The study concludes that improving automotive workshop performance requires an integrated approach involving service quality, operational efficiency, process control, and service innovation.